Socialization and Training of Maize Milk Making to the Community of Bak Dilip Village, Montasik District, Aceh Besar Regency: Sosialisasi dan Pelatihan Pembuatan Susu Jagung Pada Masyarakat Desa Bak Dilip Kecamatan Montasik Kabupaten Aceh Besar - Aprita, Ika Rezvani; Endiyani; Mulla Kemalawaty; Chairil Anwar; Irmayanti; Indra Akbar (PT. ROCE WISDOM ACEH, 2024)
Bak Dilip Village is one of the villages located in Montasik District, Aceh Besar Regency. This village has a very large agricultural land and corn crops are one of the main commodities. This community service activity aims to increase the knowledge and skills of the Bak Dilip Village Community regarding corn processing into processed corn milk products that are nutritious and have economic value. Community Service activities consist of several lecturers assisted by several students conducting surveys and analyzing the situation in the village so that problems can be identified. The survey results show that one of the problems faced by the community, namely the low knowledge of the community about processed products from corn that have high economic value. The solution to the problems faced by the community is through providing knowledge of the process of making good corn milk by utilizing the potential of natural resources in the village in improving community welfare. The Bak Dilip Village community, especially the PKK mothers, were very enthusiastic in participating in this Community Service Activity. The result of this Community Service Activity is that the community has understood the process of processing corn into corn milk, and can apply it so that it can meet nutritional needs at home and can improve the economic level of the community.